Analysis of the tensile strength on the healing of the abdominal wall of rats treated with infliximab - Lopes,João Vieira (2008)
PURPOSE: To evaluate the effects of infliximab, a murine/human chimeric monoclonal antibody, on the tensile strength of abdominal wall surgical wounds. METHODS: Sixty Wistar healthy male rats with initial body weight between 215 and 390 g and 60 and 90 days of age were randomly assigned into two groups, E (Experimental) and C (Control) with 30 animals each. Group E animals received a single subcutaneous dose of 5mg/Kg of infliximab, and Group C animals received equivalent subcutaneous volume of a solution of 0.9% NaCl. After 48h, animals from both groups were submitted to a 4 cm median incision in the abdominal wall, including all layers that had been reconstituted with continuous suture of the aponeurotic muscle and skin, with 5.0 nylon thread. Then, Group E animals were separated by simple allotment into three subgroups named E3, E7 and E14 with ten animals each, and those from group C into C3, C7, C14 and were submitted, respectively, the reoperation and euthanasia at the third, seventh and fourteenth postoperative day. The anterior abdominal wall, which was resected during reoperation, was cut with No 15 scalpel lamina perpendicularly to the surgical wound. Each specimen, in the form of a 6 cm x 2 cm strip, was fixed by the extremity so that the suture line was equidistant from the fixation points of the dynamometer, in order to undergo the tensile strength test. The dynamometer, which was gauged for each series of measures, was calibrated to apply velocity to the 25 mm/min rupture test; the rupture value was expressed in N (Newton). Prior to euthanasia, the abdominal vena cava was identified and punctured in order to collect blood for TNF-α dosage. RESULTS: The mean tensile strength found for animals from subgroups E3, E7, E14, C3, C7, C14 were, respectively, 16.03, 18.69, 27.01, 28.40, 27.22, 29.15 and 24.30 N. In the results of the multiple comparisons tests, significant differences (p<0.05) was found between subgroups E3 and E7 compared with C3, C7 and C14. CONCLUSION: The infliximab interfered in the healing of the abdominal wall wound decreasing the rupture strength in the inflammatory and proliferative phases.